2017
DOI: 10.1002/jmv.24852
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of CD38 and HLADR in HIV‐infected patients with oral lesion

Abstract: Persistent immune actiation is associated with innadequate immune recovery in HIV-patients. This study assessed the relationship between frequency of expression of cell activation markers (CD38 and HLADR) and presence of oral lesions in HIV-1 infected patients. Fifty-seven HIV-infected persons, undergoing antiretroviral treatment, were divided into three groups, according to the number of CD4 T cells and CD4 /CD8 ratio: adequate, partial, and inadequate immune restauration. All patients underwent full mouth as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…We chose several classical phenotype markers of lymphocytes including CD28 (naive marker), CD45RA (naive marker), HLA-DR (activated marker) and CD45RO (memory marker) to reflect host immunity. These phenotype markers are correlated with lymphocyte function and are known to play an important role in many diseases such as infection, tumor, and autoimmune disease [24][25][26][27]. As expected, our data demonstrated that the expression of CD28 on T cells gradually decreased with increasing age and was negatively correlated with their function.…”
Section: Discussionsupporting
confidence: 85%
“…We chose several classical phenotype markers of lymphocytes including CD28 (naive marker), CD45RA (naive marker), HLA-DR (activated marker) and CD45RO (memory marker) to reflect host immunity. These phenotype markers are correlated with lymphocyte function and are known to play an important role in many diseases such as infection, tumor, and autoimmune disease [24][25][26][27]. As expected, our data demonstrated that the expression of CD28 on T cells gradually decreased with increasing age and was negatively correlated with their function.…”
Section: Discussionsupporting
confidence: 85%
“…Besides MM and some B-cell lymphomas, increased CD38 expression can also be found in some other diseases related with T-cell expression of CD38, including rheumatoid arthritis synovial tissues [28], systemic lupus erythematosus [29], HIV infection [30] [31], and liver transplantation rejection [32]. Due to its ability to image CD38 in vivo , 89 Zr-Df-daratumumab may be preclinically applied for evaluating CD38 expression which correlated with disease diagnosis assistance and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a decrease in the incidence of dental caries following antiretroviral therapy [ 14 ]. A study among HIV-positive patients reported higher levels of immune activation markers HLA-DR and CD38 expressions in the peripheral blood when oral lesions were present [ 15 ], suggesting that oral health may significantly impact the immune response of HIV patients, including those under suppressive ART. However, HLA-DR and CD38 levels did not vary substantially according to the DMFT index.…”
Section: Introductionmentioning
confidence: 99%